Analysis of Financial Management and Supervision at Nurul Izzah Kindergarten in Medan - Harahap, Khansa Amira; Kusmilawaty; Syafina, Laylan (Jurnal Manajemen Bisnis, 2024)
This study is aimed at examining the financial management and supervision system, along with efforts to enhance them, at Nurul Izzah Kindergarten. Employing qualitative methods, such as observation, interviews, and documentation, data was gathered directly from the school's leadership. The analysis reveals shortcomings in financial management and supervision at Nurul Izzah Kindergarten. The financial budget system faces challenges with overdue tuition payments and limitations on government BOP funds. Additionally, financial supervision primarily involves internal parties, neglecting external stakeholders. Consequently, there are implications such as insufficient funds for school facilities and infrastructure, hindering the development of financial management and transparency in financial reporting.To address these issues and enhance financial management and supervision, several measures are proposed. These include establishing a competent finance team, implementing an effective accounting system, ensuring transparency in financial information, and conducting regular evaluations and improvements for the future progress of Nurul Izzah Kindergarten.